2016
DOI: 10.3390/ijms17030387
|View full text |Cite
|
Sign up to set email alerts
|

TFE3 Alleviates Hepatic Steatosis through Autophagy-Induced Lipophagy and PGC1α-Mediated Fatty Acid β-Oxidation

Abstract: Autophagy flux deficiency is closely related to the development of hepatic steatosis. Transcription factor E3 (TFE3) is reported to be a crucial gene that regulates autophagy flux and lysosome function. Therefore, we investigated the role of TFE3 in a cell model of hepatic steatosis. We constructed L02 hepatocyte lines that stably over-expressed or knocked down the expression of TFE3. Subsequently, the effects of TFE3 on hepatocellular lipid metabolism were determined by autophagy flux assay, lipid oil red O (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…(61) Lentivirus-mediated overexpression of this transcriptional regulator in hepatoma cells results in an increased association of LC3 with LDs and reductions in total cellular lipid content. (62) It is unknown, however, if similar results are observed in vivo. Similarly, knockout of TFEB, another transcriptional regulator of lysosome biogenesis, also resulted in an accumulation of hepatocellular LDs.…”
Section: Regulation Of Hepatic Lipophagymentioning
confidence: 95%
See 1 more Smart Citation
“…(61) Lentivirus-mediated overexpression of this transcriptional regulator in hepatoma cells results in an increased association of LC3 with LDs and reductions in total cellular lipid content. (62) It is unknown, however, if similar results are observed in vivo. Similarly, knockout of TFEB, another transcriptional regulator of lysosome biogenesis, also resulted in an accumulation of hepatocellular LDs.…”
Section: Regulation Of Hepatic Lipophagymentioning
confidence: 95%
“…Transcriptional regulation of lipophagy may thus be mediated by factors such as the transcription factor TFE3, which binds to promoters key to the process of lysosomal biogenesis . Lentivirus‐mediated overexpression of this transcriptional regulator in hepatoma cells results in an increased association of LC3 with LDs and reductions in total cellular lipid content . It is unknown, however, if similar results are observed in vivo .…”
Section: Regulation Of Hepatic Lipophagymentioning
confidence: 99%
“…TFE3 also regulates lipophagy in the liver. Specifically, liver-specific ablation of TFE3 promotes steatosis, and overexpression reduces steatosis via lipophagy [76]. In contrast, adipose-specific overexpression of TFE3 increases adiposity [77], which may be explained by studies showing that autophagy promotes adipocyte differentiation [7880].…”
Section: Regulation Of Lipophagymentioning
confidence: 99%
“…Members of this family including TFEB or TFE3 can both induce lipophagy and reduce hepatic lipid accumulation. In contrast, the absence of either TFEB or TFE3 increases lipid accumulation [38,39]. TFEB/TFE3 also target the peroxisome proliferator-activated receptors (PPAR) and PPAR-gamma coactivator-1 family of transcription factors and coactivators.…”
Section: Regulation Of Lipophagymentioning
confidence: 99%
“…TFEB/TFE3 also target the peroxisome proliferator-activated receptors (PPAR) and PPAR-gamma coactivator-1 family of transcription factors and coactivators. These assist in driving transcription of mitochondrial and fatty acid oxidation genes allowing full utilization of the fatty acid products of lipophagy [38,39]. Two other recent studies identified farnesoid-X receptor (FXR) as a transcriptional repressor of autophagy (Fig.…”
Section: Regulation Of Lipophagymentioning
confidence: 99%